EPIDEMIOLOGICAL CONNECTIONS BETWEEN SCREENS AND MOVEMENT, SEDENTARY BEHAVIOR, PHYSICAL (IN)ACTIVITY AND HEALTH HABITS - Santos, Marco Antonio Ferreira dos (2024)
This study analyzed physical activity patterns, sedentary behaviors and exposure to screens in students from four school units in Rio de Janeiro. The objective was to provide insights for the development of health promotion strategies through physical activities and sports (AFES). Using the IPAQ questionnaire, data were collected from 1668 students, with an average age of approximately 13.8 years from all grades of primary and secondary education. Statistical tests were used for analysis. The results indicated that students walked, on average, more than 10 minutes per day on 4 days (male) and 3 days (female), with 75 minutes (male) and 69 minutes (female) of daily walking, respectively. The average of moderate activities was 91 minutes per day, while vigorous activities totaled, on average, 126 minutes (male) and 71 minutes (female). Significant sex differences were observed in daily walking, moderate and vigorous activities, and weekly inactivity time. Variations were also identified between school units, indicating differences in the application of AFES. The positive and significant correlation between the total number of days and the time of vigorous activities (ρ = 0.65; p ≤ 0.05) highlights the importance of different strategies. With regard to inactivity and exposure to screens, the average time during the week was 574 minutes, while on weekends it was 510 minutes. These results contribute to direct health promotion policies, emphasizing the need for personalized approaches for students in Rio de Janeiro.